The Effectiveness of Exercise on Sleep Quality in the Elderly: Literature Review - Maduratna Arinda Alif; Zainal Abidin; Anggia Astuti (STIKes Kepanjen, 2022)
Introduction: Insomnia in the elderly can cause weakness, dizziness, and fatigue. In addition, the psychological impact of poor sleep quality is anxiety, irritability, disturbed concentration, and stress which can increase the risk of suicide. Poor sleep quality can cause nursing problems Sleep Pattern Disorders. One of the interventions that can be given is education on rest activities, namely physical activity or sportsMethod: The method used to achieve a literature review. The literature search was conducted on the PubMed, Science Direct, Google ScholarResult: The results of 10 articles on the types of exercise used include aerobic exercise, elderly exercise, sports, low-intensity and high-intensity physical activity. most articles do exercise for 30 minutes, 2-7x a week, for 3 weeks. The quality of sleep in the elderly has increased after doing sports exercises with an ap value <0.05.Conclusion: Exercise can be an alternative to improve sleep quality in the elderly Keywords :Elderlysleep quality,Exercise